USE OF MODERN INFORMATION TECHNOLOGIES IN TEACHING PHYSICS - Fayzieva Kholida Asadovna (Scholar Express Journal, 2023)
Today's modern world encourages to look at every detail in the field of education with a modern eye. Including, teaching each subject to students in such a way as to incorporate modern innovative technologies in addition to its educational methodology is one of the current issues. This article describes the importance of physics in the world community and the use of modern information technologies in teaching this science to students
Keywords: Computer technologies; virtual laboratory; multimedia tools; Physics at school